Analysis of factors affecting mortality outcome in ischemic bowel disease- a study of 50 cases - H Jathar, Advait; S Kamath, Bharat; A Rao, Shilpa (International Journal of Medical Research and Review, 2016)
Introduction: Ischemic bowel disease is the outcome of inadequate supply of oxygen to the intestine leading to ischemia having a plethora of symptoms and signs which are often inconspicuous leading to delayed diagnosis exacerbating already poor patient outcomes. There is a definite need to classify patients into high and low risk categories, so that intensive monitoring and care can be delivered to improve mortality outcome. Methods: We have done a prospective study of 50 adult cases of ischemic bowel disease confirmed on radiology, intra-operative findings and histopathology and compared the mortality and severity of disease with various patient parameters and analyzed significant correlations if any. Results: Majority of patients were adult males above age of 50 years with acute presentation. Hypertension and diabetes were commonly seen. Clinically, tenderness and tachycardia were common. ECG was abnormal in 72% patients. On imaging, thrombotic SMA involvement was present in majority of patients. Therapeutically, 90% patients were explored with a high mortality rate (71%) commonly the cause being sepsis (47%). Overall mortality was 64%. Small bowel was commonly affected. Majority of patients suffered from sepsis requiring ionotropic and ventilatory support. All patients with SMV thrombosis survived. Raised serum creatinine and altered pH were strongly associated with mortality. Also patients with ischemic bowel segment more than 80cm were at a high risk of death. Conclusion: The need for a scoring system based on parameters discussed has to be addressed, to stratify patients who will require critical and specialized intensive care and improve mortality outcomes.